Development of a portable microfluidic system for monitoring ions river water - Ong, Chee Keong (2012)
Nowadays, there is a growing demand for predictive models that are capable of predicting future trends in water quality which is constantly being affected by environmental changes and industrialisation. The presence of various nutrient contaminants in surface water poses a serious threat to human health. The initial step for the development of this predictive model is to have an in situ monitoring system that provides high frequency screening and monitoring of nutrients in surface water. At present, the conventional in situ monitoring systems available are too cumbersome, expensive and laborious. The main aim of this project was to develop a portable and automated miniaturised total analytical system (μTAS) monitoring system that could provide in situ river water nutrient measurements over a wide range of analytes such as cations (Na⁺, K⁺, Ca²⁺, Mg²⁺, NH₄⁺) and anions (Cl⁻, NO₂⁻, NO₃⁻, SO₄²⁻, PO₄³⁻). The contribution of this work to the overall project was to integrate sample pre-treatment procedures on-chip to allow direct and reproducible analysis of real samples and to investigate the possibility of fabricating an anion exchange column through immobilisation with different ion exchangers using a self-fabricated silica monolithic column. A combination of on-chip sample filtration and sample introduction system was investigated using potassium silicate frit and electrophoretic injection to selectively extract the analytes prior to introduction into the microfluidic system. The frits were optimised and proven to possess high mechanical stability and flow resistance against hydrodynamic and hydrostatic flows. Sodium ions were successfully migrated into the microfluidic system through the frit by electrophoretic flow with ion migration efficiency of 26%. Despite the low ion migration efficiency obtained, the results demonstrated the potential of coupling the sample filtration frit with sample introduction system in a microfluidic chip to prevent passage of large particulates into the system causing system blockage. Isotachophoresis (ITP) is one of the most widely reported on-chip sample pre-concentration techniques but due to the complexity of the ternary buffer systems in ITP, introduction of these buffers in an appropriate and cost-effective approach would be difficult. An investigation of a simple miniaturised gel supported ITP system was conducted where all the necessary buffers were encapsulated in agarose gel and pre-loaded onto a microfluidic chip. A proof of principle experiment was conducted in a “goal post” system and sodium ions were shown to be able to migrate through the gel encapsulated buffer system. However, implementation of the experiment in the microfluidic chip was unsuccessful due to occurrence of gel deformation. Preliminary investigation of fabricating an anion exchange column using a self-fabricated silica monolithic column was conducted based on solid phase extraction (SPE). Two different ion exchangers, chitosan and lysine, were investigated due to their high content of amino groups. Lysine was shown to be successfully immobilised onto the silica surface and to have reasonable extraction efficiency of 62% in extracting nitrate ions. Chitosan, however, failed to show any positive result, this may be due to an unsuccessful functionalisation procedure or poor pre-conditioning of the column. The findings obtained in this thesis contributed to the main aim of the project by demonstrating the potential of coupling a sample filtration frit with a sample introduction system which allowed the in situ μTAS monitoring system to extract the analytes from the sample matrix prior to introduction into the system. This is crucial as these real samples contain large particulates that can cause serious operational problems such as system blockage. In addition, due to the high cost of commercial silica monolithic exchange column, the work presented indicated the potential for self-fabricating the ion exchange silica monolithic column, which is more cost-effective.
HydraID: hull:6343
Keywords: Chemistry